Multi‐Scale Density Structures in the Plasmaspheric Plume During a Geomagnetic Storm. Issue 3 (28th March 2022) - Nishimura, Y.; Goldstein, J.; Martinis, C.; Ma, Q.; Li, W.; Zhang, S. R.; Coster, A. J.; Mrak, S.; Semeter, J. L.; Nishitani, N.; Ruohoniemi, J. M.; Shepherd, S. G.
Abstract: Evolution of large‐scale and fine‐scale plasmaspheric plume density structures was examined using space‐ground coordinated observations of a plume during the 7–8 September 2015 storm. The large‐scale plasmaspheric plume density at Van Allen Probes A was roughly proportional to the total electron content (TEC) along the satellite footprint, indicating that TEC distribution represents the large‐scale plume density distribution in the magnetosphere. The plasmaspheric plume contained fine‐scale density structures and subauroral polarization streams (SAPS) velocity fluctuations. High‐resolution TEC data support the interpretation that the fine‐scale plume structures were blobs with ∼300 km size and ∼500–800 m/s in the ionosphere (∼3, 000 km size and ∼5–8 km/s speed in the magnetosphere), emerging at the plume base and drifting to the plume. The short‐baseline Global Navigation Satellite System receivers detected smaller‐scale (∼10 km in the ionosphere, ∼100 km in the magnetosphere) TEC gradients and their sunward drift. Fine‐scale density structures were associated with enhanced phase scintillation index. Velocity fluctuations were found to be spatial structures of fine‐scale SAPS flows that drifted sunward with density irregularities down to ∼10 s of meter‐scale. Fine‐scale density structures followed a power law with a slope of ∼−5/3, and smaller‐scale density structures developed slower than the larger‐scale structures. We suggest that turbulent SAPS flows created fine‐scale density structures and their cascading to smaller scales. We also found that the plume fine‐scale density structures were associated with whistler‐mode intensity modulation, and localized electron precipitation in the plume. Structured precipitation in the plume may contribute to ionospheric heating, SAPS velocity reduction, and conductance enhancements. Plain Language Summary: A plume of cold plasma circulates in the system during geomagnetic storms, and it is important for global positioning system (GPS) signal scintillation at mid‐latitudes of the Earth. We show that the plume contains fine‐scale density structures across multiple‐scales, and reveal their 2‐d structure and motion using GPS remote sensing and multiple satellites. The network of GPS receivers showed that the fine‐scale plume structures were blobs with hundreds of km size in the ionosphere, and GPS signal scintillation was highly correlated with the fine‐scale density structures. Radar observations identified a close relation between the fine‐scale density and fast plasma streams. The plume density structures formed first at large‐scales and then small‐scale density structures emerged near the peak of the geomagnetic storm. We suggest that fast plasma streams created fine‐scale density structures and their turbulent cascading to smaller scales. Key Points: Two dimensional structure and motion of fine‐scale plume density has been revealed by Van Allen Probes‐defense meteorological satellite program‐Swarm‐global positioning system conjunction Fine‐scale subauroral polarization streams flows are related to fine‐scale density and are suggested to create turbulent density cascading Fine‐scale density contributes to waves, precipitation, heating, and scintillation